The impact of technological innovation Capabilities on competitive advantage And firm performance : an empirical Study in the automotive industry In Malaysia - Faridah, Taju Rahim (2020)
Innovation plays an important role in determining a firm’s success and survival in sustaining its global competitiveness in the long-term. Nevertheless, there is a limited number of studies on technological innovation capabilities (TIC), especially in the automotive industry in Malaysia. Accordingly, this study attempts to fill the gap in the current analysis on the technological innovation capabilities (TIC) in the automotive industry in Malaysia. This study examines the impact of technological innovation capabilities, i.e. R&D capability (RDC), manufacturing capability (MC), networking capability (NC), and human resource capability (HRC) on competitive advantage (CA) in terms of cost advantage (COA), differentiation advantage (DA), product innovation (PT) and process innovation (PS), and firm performance in the automotive industry in Malaysia. Drawing upon the Resource-Based View (RBV) of the firm and the Dynamic Capabilities View (DCV), a conceptual framework is developed. A quantitative research approach was used to conduct this study, in which 136 respondents from the automotive industry were surveyed through convenience and purposive sampling procedures. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used to test the study’s hypotheses using WarpPLS 6.0 software. The findings revealed that RDC, MC, NC, and HRC as TICs dimensions, and COA, DA, PT, and PS as CA dimensions, are important factors for the performance of firms in the automotive industry in Malaysia. Four conclusive findings are derived from the study. First, with respect to the direct effect of TICs dimensions on CA dimensions, the study reveals that all TICs dimensions (RDC, MC, NC, and HRC) have an influence on COA. Whereas RDC, NC, and HRC positively and significantly influence DA, but MC negatively influence DA. Only HRC has an influence on PT. However, for PS, only MC and NC significantly impact PS. Second, regarding direct impact of TICs dimensions on firm performance, the study confirms that RDC, MC, and NC positively and significantly impact firm performance, except for HRC, which has no significant effect on firm performance. Third, competitive advantage dimensions, such as DA, PT, and PS have a significant impact on firm performance. Fourth, the results also show that DA fully mediated the relationship between HRC and firm performance, while DA also partially mediated the relationship between NC and firm performance. This indicates that improving CA, especially in terms of DA, is crucial in achieving high firm performance. Therefore, this research shows the importance of TICs dimensions and CA dimensions in improving firm performance in the automotive industry. These findings have theoretical contributions as well as practical and policy implications. These contributions and implications are also significant findings for firms in the automotive industry in Malaysia. The study contributes firstly, to the body of knowledge by examining the mediating roles of CA. Secondly, it complements the resource-based view (RBV) theory and Dynamic Capability View regarding the interconnection between TIC dimensions and firm performance. Thirdly, it particularly benefits the industrial practitioners, where the study provides the practical information of the automotive industry. Fourthly, the practitioners are also at an advantage when they are aware of the technological innovation strategies, highlighted in this study, of overcoming the anticipated challenges in the business. Finally, some limitations are also acknowledged, that indicate future research directions.